2020
DOI: 10.4269/ajtmh.20-0282
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Schistosoma mansoni Infection in a Nonhuman Primate from St. Kitts More than 50 Years after Interruption of Human Transmission

Abstract: Transmission of Schistosoma mansoni was interrupted on St. Kitts, a Caribbean island, in the 1950s. With no reported cases since that time and most Biomphalaria spp. snail populations eliminated based on surveys in the 1970s, S. mansoni has been considered eliminated on St. Kitts. In 2019, S. mansoni eggs were found in an African green monkey (Chlorocebus aethiops sabaeus) that originated from St. Kitts. Nonhuman primate (NHP) infections have been considered incidental to human infections, with infections in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Additionally, while visiting freshwater habitats across the island, including Cul de Sac, we were struck by the limited extent to which St. Lucians now seem to depend on surface waters for bathing or clothes washing, thereby diminishing the likelihood of exposure to infection should the parasite be present. Finally, we note that the possibility remains that there are isolated foci of infection maintained by rodent or other reservoir hosts, 43 45 though this seems less likely to be an issue of concern given the rarity of B. glabrata , the lack of supporting eDNA evidence, and the potential difficulty of short-lived rodents to maintain transmission under such circumstances.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, while visiting freshwater habitats across the island, including Cul de Sac, we were struck by the limited extent to which St. Lucians now seem to depend on surface waters for bathing or clothes washing, thereby diminishing the likelihood of exposure to infection should the parasite be present. Finally, we note that the possibility remains that there are isolated foci of infection maintained by rodent or other reservoir hosts, 43 45 though this seems less likely to be an issue of concern given the rarity of B. glabrata , the lack of supporting eDNA evidence, and the potential difficulty of short-lived rodents to maintain transmission under such circumstances.…”
Section: Discussionmentioning
confidence: 92%
“…Despite the prevailing perception of schistosomiasis as a predominantly human disease [ 10 , 36 ], the Schistosoma genus has shown a remarkable ability to diverge and adapt to new hosts and habitats that has persisted beyond its evolutionary origins. This is evident not only among members of the Asian S. japonicum clade, but also among several species of both African clades, as exemplified by the establishment and persistence of S. mansoni in the Caribbean [ 38 , 43 , 44 ], and the recent expansion of S. haematobium × S. bovis hybrids into Europe ([ 45 ] but see [ 9 ]). This adaptability presents increasingly recognized challenges to the control and elimination of schistosomiasis and epitomizes the necessity for a holistic One Health approach.…”
Section: Introductionmentioning
confidence: 99%
“…in 2014, the infection prevalence documented in rodents, goats and dogs was above 9% in Hunan province [ 85 ]). Elsewhere, the finding in 2019 of a green monkey infected with S. mansoni in St Kitts—where schistosomiasis was thought to have been eliminated in the 1970s—raises several questions, including reintroduction of the parasite to the island, or the existence of a sylvatic cycle maintained by non-human primates [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since their introduction their numbers have exploded, and due to the damage they cause to a variety of crops/fruits, native flora, and wildlife, St. Kitts vervets are considered pests by local farming communities contrary to other government agencies who consider their presence on the Island an important tourist attraction. Recent surveys have shown that St. Kitts vervets are a host for multiple human-pathogenic helminths including Trichuris trichiura , Schistosoma mansoni , and S. fuelleborni , in addition to other protozoal, bacterial, and viral pathogens ( Gallagher et al, 2019 ; Ketzis et al, 2020 ; Cruz et al, 2021 ). It is possible that vervets originally introduced to St. Kitts brought an African variety of S. fuelleborni to the island, although a detailed molecular analysis of S. fuelleborni types infecting St. Kitts vervets has not been performed.…”
Section: Introductionmentioning
confidence: 99%